KARAKTERISTIK BATUAN SEDIMEN BERDASARKAN ANALISIS PETROGRAFI PADA FORMASI KALIBENG ANGGOTA BANYAK - Purasongka, Novianti Wahyuni; Syafri, Ildrem; Jurnaliah, Lia (Bulletin of Scientific Contribution, 2015)
Administratively, the research areas included in the district of Semarang, Central Java Province. This research was conducted at Jeragung River with the object of claystone and sandstone. In physiographic, rocks in the study area are in Kendeng Basin, and parts of Anggota Banyak Kalibeng Formation. This study aims to determine the characteristics of sedimentary rocks mainly sandstones, based on petrographic analysis to determine the source of the sediment and diagenesis processes that formed. Based on observations of six sandstone samples from areas of research included in Feldspatic Wacke. Provenance analysis of six samples of sandstone with using Dickinson and Suczek triangles, shows the origin of sediment is arc magmatic. Diagenesis phase which occurs is eogenesis characterized by compacting and leaching, mesogenesis marked by cementation and recrystallization, as well as the replacement and deformation marks telogenesis process.